Total cancer risk estimates from measured concentrations of volatile organic compounds in industrialized southeastern Louisiana - Ellis S. Robinson; Amira Yassine; Shivang Agarwal; Mina W. Tehrani; Sara N. Lupolt; Andrea A. Chiger; Carolyn Gigot; Megan S. Claflin; Brian M. Lerner; Tara I. Yacovitch; Joseph R. Roscioli; Scott C. Herndon; et al. (Proceedings of the National Academy of Sciences, 2025)
Communities in southeastern Louisiana are subject to disproportionate environmental health burdens, including elevated risk for cancer, from emissions of industrial hazardous air pollutants (HAPs). However, there are few ambient measurements (or none) of various HAPs in the heavily industrialized corridor between Baton Rouge and New Orleans (BR-NO). We measured 17 carcinogenic volatile organic compounds using fast-response in situ instrumentation aboard a mobile laboratory. Using spatially resolved concentrations, we estimate cancer risk in 15 census tracts along an 81 km-long stretch of the BR-NO corridor. In 14 of 15 tracts, our estimates of total cancer risk were higher (range: 0.9 to 11.6 × ; median: 5 × ) than those from the U.S. Environmental Protection Agency’s (USEPA) 2020 Air Toxics Screening Assessment (AirToxScreen). Our maximum estimate for total tract-level cancer risk was 560-in-one million excess cancer cases, far exceeding the upper limit of USEPA’s acceptable risk range (100-in-one million). This discrepancy is largely explained by differences between measured vs. modeled ethylene oxide concentrations, though there are important contributions from a number of additional HAPs. Our risk estimates are dominated by ethylene oxide, which contributes between 39.5 and 92.2% of total cancer risk across all tracts; chloroprene (0.2 to 36.8%); and formaldehyde (4.1 to 14.6%). AirToxScreen also identifies these three compounds as primary drivers of risk in this location. Together, these three compounds account for between 63 and 96.9% of total cancer risk. There is substantial spatial variability in total cancer risk and the relative contribution of each HAP, both between and within tracts. These data substantiate claims that the region has high HAPs-related cancer risk and quantify which individual HAPs are of highest concern.